Feminist Periodicals, v. 39, no. 1 (Winter 2019) - (:unkn) unknown (University of Wisconsin System Women's Studies Librarian's Office, 2019)
Sub-title: A Current Listing of Contents.
Table of contents periodical
Keywords: Women's Studies; Periodicals; Tables of Contents; Resources; Gender; Feminism; Lesbian Periodicals--Index; Women's Periodicals--Index